PENGUJIAN EFEKTIVITAS EKSTRAK KULIT BATANG Rhizophora mucronata SEBAGAI ANTIBAKTERI UNTUK MENCEGAH INFEKSI BAKTERI Streptoccocus iniae PADA IKAN NILA - Satriyadi Satriyadi; Dwi Suryanto; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
This research was aimed to know the antimicrobial potential of R. mucronata bark extract against S. iniae pathogenic bacteria, determine their toxicity to tilapia (Oreochromis niloticus), as well as determine the effect of immersion bark extract R. mucronata stem against the survival of tilapia fish seeds infected S. iniae bacteria. Extraction is done by maceration single use methanol, ethyl acetate and n-hexane. Tests conducted bacterium S. iniae characteristics and returns the bacterial virulence. Toxicity tested bark extract R.mucronata with a concentration of 0 ppm, 125 ppm, 250 ppm, 375 ppm and 500 ppm, the mortality rate of fish in maing each concentration is 0%, 20%, 56.67%, 86.67%, 100% and obtained LC50 at 195.39 ppm. The extract used to challenge test was R. mucronata bark extract with ethyl acetate solvent. Tilapia were used as much as 350 tails with size 1-2 cm aged 1-2 weeks and infected with the bacterium S. iniae density of 107 CFU / ml by immersion. The test results bark extract R.mucronata rod solvent ethyl acetate that concentration had ability as an antibacterial that was at a concentration of 19.54 ppm with results tilapia fish survival percentage was 100%. Immersion bark extract R.mucronata rods significant (P<0.05) on survival seeds tilapia infected bacteria S. iniae. Calculation of the number of colonies bacteria with methods TPC (Total Plate Count). Reduced the number of bacterial colonies after immersion of the average rate of 3.52 x 104 CFU / ml to 3.38 x102 CFU / ml.Keywords: Extraction, Streptococcus iniae, Rhizophora mucronata, Tilapia, Test toxicity